Polar nano-clusters in nominally paraelectric ceramics demonstrating high microwave tunability for wireless communication - Zhang, Hangfeng; Giddens, Henry; Yue, Yajun; Xu, Xinzhao; Araullo-Peters, Vicente; Koval, Vladimir; Palma, Matteo; Abrahams, Isaac; Yan, Haixue; Hao, Yang (Journal of the European Ceramic Society, 2020)
Nominally paraelectric Ba0.6Sr0.4TiO3 ceramics with a superior tunability and low loss at microwave frequency have been fabricated, through grain size control of polar nano-clusters. A prototype electrically small resonant antenna, using the bulk dielectric material, has been constructed and exhibits a reconfigurable resonant frequency with the application of a DC bias. [Display omitted] Dielectric materials, with high tunability at microwave frequencies, are key components in the design of microwave communication systems. Dense Ba0.6Sr0.4TiO3 (BST) ceramics, with different grain sizes, were prepared in order to optimise the dielectric tunability via polar nano cluster effects. Dielectric permittivity and loss measurements were performed at both high and low frequencies and were supported by results from X-ray powder diffraction, scanning and transmission electron microscopies, Raman spectroscopy and piezoresponse force microscopy. The concentration of polar nano clusters, whose sizes are found to be in the range 20–50 nm, and the dielectric tunability increase with increasing grain size. A novel method for measurement of the microwave tunability in bulk dielectrics is presented. The highest tunability of 32 % is achieved in ceramics with an average grain size of 10 μm. The tunability of BST ceramics with applied DC field is demonstrated in a prototype small resonant antenna.